2009
DOI: 10.4067/s0717-92002009000300003
|View full text |Cite
|
Sign up to set email alerts
|

Aporte de hojarasca en bosques del predelta del río Paraná (Argentina)

Abstract: INTRODUCCIÓNGran parte de la materia orgánica del suelo (MOS) deriva de la humificación de los residuos orgánicos que llegan al suelo tras su abscisión: hojas, ramas, flores, frutos y demás estructuras vegetales (incluso árboles enteros) que conforman la hojarasca. Esta MOS, tras su mineralización, libera bioelementos que pueden ser reabsorbidos por las plantas, contribuyendo así al ciclo biogeoquímico. Esta liberación de nutrientes, por tanto, está determinada, en última instancia, por las características gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 12 publications
(16 reference statements)
0
5
0
3
Order By: Relevance
“…Regarding the relationship between seasonal litterfall production pattern and environmental variables, Aceñolaza et al (2009) observed significant correlations between litterfall production and water level variation of the Paraná River in forests of its alluvial plain basin (eastern Argentina). Nevertheless, climatic variables, considered as conditioning factors (such as precipitation, wind, or temperature), did not influence significantly the seasonal pattern of litterfall in our study during the studied years.…”
Section: Annual Contribution By the Fraction Named 'Other'mentioning
confidence: 98%
See 2 more Smart Citations
“…Regarding the relationship between seasonal litterfall production pattern and environmental variables, Aceñolaza et al (2009) observed significant correlations between litterfall production and water level variation of the Paraná River in forests of its alluvial plain basin (eastern Argentina). Nevertheless, climatic variables, considered as conditioning factors (such as precipitation, wind, or temperature), did not influence significantly the seasonal pattern of litterfall in our study during the studied years.…”
Section: Annual Contribution By the Fraction Named 'Other'mentioning
confidence: 98%
“…The contribution of this fraction is difficult of establish, by the majority of it could be associated with the presence/absence of shrub species, mainly of the genus Baccharis; a relatively high contribution of the "others" fraction (approximately 20 % of total production) can be expected in mixed forests (Aceñolaza et al, 2009), whose shrub layer has many species of the Asteraceae family.…”
Section: Annual Contribution By the Fraction Named 'Other'mentioning
confidence: 99%
See 1 more Smart Citation
“…La caída de hojarasca es importante ya que pone el sistema suelo-planta en relación funcional (Belmonte, Romero & López, 1998); es un proceso relacionado con la transferencia de energía y ciclos biogeoquímicos (Aceñolaza, Zamboni & Gallardo, 2009;Santa Regina & Gallardo, 1989), materia orgánica (Liu et al, 2004) y representa el mayor flujo de nutrientes de la vegetación al suelo (Berg & Meentemeyer, 2001;González et al, 2008; Pérez-Suárez, Arredondo-Moreno, Huber-Sannwald, & Vargas-Hernán-dez, 2009). La hojarasca ha sido utilizada como una medida de la productividad primaria neta (Vargas & Varela, 2007), manteniendo la biodiversidad biológica (Carnevale & Lewis, 2001, Zamboni & Aceñolaza, 2004.…”
Section: Introductionunclassified
“…Litterfall is important because it sets the soil-plant system in functional relationship (Belmonte, Romero & Ló-pez, 1998); this process is related to the transfer of energy and biogeochemical cycles (Aceñolaza, Zamboni & Gallardo, 2009;Santa Regina & Gallardo, 1989), organic matter (Liu et al, 2004) and represents the greatest flow of plant nutrients to soil (Berg & Meentemeyer, 2001;González et al, 2008;Pérez-Suárez, Arredondo-Moreno, Huber-Sannwald, & Vargas-Hernández, 2009). Litterfall has been used as a measure of the net primary productivity (Vargas & Varela, 2007), maintaining the biological biodiversity (Carnevale & Lewis, 2001, Zamboni & Aceñolaza, 2004.…”
Section: Introductionmentioning
confidence: 99%